Efisiensi Air di Pesantren melalui Penerapan Sunnah Nabi dan Teknologi Terapan - Ariesman M (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2018)
Water is a primary necessity for the process of life on earth, so there is no life if there is no water in the earth as Allah says "And out of the water we made all things alive". It is estimated that around 321 million Indonesians will experience water scarcity by 2025. Population growth is not proportional to water availability, industrial growth, and wasteful public behavior is the main cause. Pondok pesantren which has about 3,759,198 santri throughout Indonesia will be able to feel the impact if the pattern of water use is not in use sparingly. The application of the Sunnah of the Prophet sallallaahu alaihi wasallam and applied technology is very eï¬€ective in saving water. The number of students as much as that by using the wudu 1 mud 'can save 8,693,145 liters and if in rupiah it is as much as Rp. 45.239.129.